The Digital Imaging Workstation - Arenson, Ronald L. (Springer-Verlag, 2003)

(untitled)
Picture archiving and communication systems (PACS) are expected to convert film-based radiology into a computer-based digital environment, with associated cost savings and improved physician communication. The digital workstation will be used by physicians to display these “soft-copy” images; however, difficult technical challenges must be met for the workstation to compete successfully with the familiar viewbox. Issues relating to image perception and the impact on physicians’ practice must be carefully considered. The spatial and contrast resolutions required vary according to imaging modality, type of procedure, and class of user. Rule-based software allows simple physician interaction and speeds image display. A consensus appears to be emerging concerning the requirements for the PACS workstation. Standards such as the American College of Radiology/National Electrical Manufacturers’ Association Digital Imaging and Communication Standard are facilitating commercial applications. Yet much careful study is needed before PACS workstations will be fully integrated into radiology departments.